2014
DOI: 10.1080/01694243.2014.958334
|View full text |Cite
|
Sign up to set email alerts
|

Aging effect in the adhesion of a PC/CPVC arrangement for application in thermo-solar collectors

Abstract: This work studies the aging of materials in a polycarbonate/chlorinated polyvinyl chloride (PC/CPVC) arrangement, used in a flat plate thermo-solar collector. Typically, PC is used as an absorbing surface and CPVC in entrance and exit heads of the flow, which in this case is water. In this study, two types of methacrylate adhesives were used to bond both plastics, denominated MP and SK. The experiment comprised a study of adhesion behavior between these polymers and the adhesives, in contact with distilled wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Moreover, it is important to maintain a low temperature in the collector, particularly in collectors made from plastic materials, such as those proposed by Refs. [14] and [16], where it has been observed that a high temperature can have an adverse effect on a collector made from these materials, giving rise to structural failures [17]. In solar plants mass flow manipulation is used to match the temperature requirements of load processes [18,19], which has been found to work at a smaller scale also.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, it is important to maintain a low temperature in the collector, particularly in collectors made from plastic materials, such as those proposed by Refs. [14] and [16], where it has been observed that a high temperature can have an adverse effect on a collector made from these materials, giving rise to structural failures [17]. In solar plants mass flow manipulation is used to match the temperature requirements of load processes [18,19], which has been found to work at a smaller scale also.…”
Section: Introductionmentioning
confidence: 98%